2003
DOI: 10.1038/nature01682
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Notch and Delta genes in spider segmentation

Abstract: It is currently debated whether segmentation in different animal phyla has a common origin and shares a common genetic mechanism. The apparent use of different genetic networks in arthropods and vertebrates has become a strong argument against a common origin of segmentation. Our knowledge of arthropod segmentation is based mainly on the insect Drosophila, in which a hierarchical cascade of transcription factors controls segmentation. The function of some of these genes seems to be conserved among arthropods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
214
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(231 citation statements)
references
References 27 publications
11
214
1
2
Order By: Relevance
“…It is generally believed that biological processes are controlled by activating a hierarchical cascade of interdependent regulators, such as transcription factors or protein kinases [26,27]. By illustrating that a miRNA can regulate the biogenesis of other miRNAs, the results of the present study suggest that certain miRNAs can serve as a novel group of interdependent regulators at post-transcriptional level, in a so-called "miRNA hierarchy system" (Supplementary information, Figure S9).…”
Section: Discussionmentioning
confidence: 75%
“…It is generally believed that biological processes are controlled by activating a hierarchical cascade of interdependent regulators, such as transcription factors or protein kinases [26,27]. By illustrating that a miRNA can regulate the biogenesis of other miRNAs, the results of the present study suggest that certain miRNAs can serve as a novel group of interdependent regulators at post-transcriptional level, in a so-called "miRNA hierarchy system" (Supplementary information, Figure S9).…”
Section: Discussionmentioning
confidence: 75%
“…A more complicated issue is that of segmentation. Segmentation is distinct from serial repetition, and the Delta-Notch signalling system is involved in defining segmental boundaries in vertebrates and spiders (where Notch patterns the ectoderm, rather than the mesoderm, as in vertebrates) (Stollenwerk et al 2003;Tautz 2004;Pueyo et al 2008;reviewed in Erwin 2006). While the Notch signalling pathway is present in cnidarians, the Delta-Notch cascade appears to be a later innovation.…”
Section: The Ediacaran Fauna In Light Of Developmentmentioning
confidence: 99%
“…The complexity of this toolkit varies as new studies and broader comparative studies are reported, but minimally includes the following: anterior/posterior (A/P) patterning with seven or eight HOX genes (de Rosa et al 1999;Balavoine et al 2002), and the associated microRNA responsible for inhibiting translation of HOX mRNAs (de Robertis 2008); the HOX genes part of a larger super cluster of at least eight other ANTP-class genes including the ParaHox and NK cluster genes (Butts et al 2008); dorsal/ventral (D/V) patterning controlled by the sog/chordin dpp/ BMP2/4 system (Arendt & Nubler-Jung 1994;De Robertis & Sasai 1996); anterior patterning via ems/ Emx and otd/Otx and a tripartite brain (Arendt & Nubler-Jung 1999;Reichert & Simeone 2001;Arendt et al 2008) with posterior patterning via evenskipped/evx and caudal/cdx; segmentation through engrailed and Delta -Notch (Holland et al 1997;Balavoine & Adoutte 2003;Stollenwerk et al 2003;Tautz 2004); eye formation controlled by a dense network of genes, including Pax6 and ey (Quiring et al 1994;Halder et al 1995;Gehring 2004), but see Arendt et al (2004) and Fernald (2000); endoderm formation and a regionalized through gut via GATA transcription factors, brachyury and goosecoid (Arendt et al 2001); heart formation via Nkx2.5/tinman (Harvey 1996;Bodmer & Venkatesh 1998;Olson 2006); and distal-less involvement in appendage formation (Panganiban et al 1997;Panganiban & Rubenstein 2002;Pueyo & Couso 2005). The pattern of acquisition of microRNAs tracks increasing morphological complexity and provides important information on the evolution of developmental control (Sempere et al 2006;Gimson et al 2008;Wheeler et al 2009).…”
Section: *Erwind@siedumentioning
confidence: 99%
“…Typically if variation exists in segment period, it is simply a gradual decrease in segmentation rate as segmentation 'winds down' in the posterior of the embryo 6 or a brief initial period of rapid addition prior to a more regular rate 7 . A clock mechanism for regulating segmentation has recently been extended to sequentially segmenting arthropods [8][9][10][11][12][13] . Support for a clock includes a clear demonstration of molecular oscillations in the flour beetle, Trobolium casteneum 14 .…”
mentioning
confidence: 99%